INFLAMMATORY COMPLICATIONS AFTER TOOTH EXTRACTION IN A PATIENT WITH MYASTHENIA GRAVIS - CASE REPORT - Zornitsa Mihaylova; Radomir Ugrinov; Evgeniy Aleksiev; Pavel Stanimirov (Peytchinski Publishing, 2019)
Myasthenia gravis (MG) is an antibody-mediated autoimmune disorder of the neuromuscular junction. We report a case of a 34-year-old female myasthenic patient with inflammatory complications after extraction of mandibular 1st and 3rd molars. Myasthenia gravis (MG) has been diagnosed more than 10 years ago. Routine dental management in myasthenic patients is expected to be unsafe and even life-threatening. Special management considerations, as well as advice and precautions are required with which all oral health providers should be sufficiently informed. To avoid complications in patients with MG we recommend oral surgical procedures to be performed in a hospital-based maxillofacial surgery clinic.